Putting the Disulfide Bridge at Risk: How UV‐C Radiation Leads to Ultrafast Rupture of the S‐S Bond. Issue 21 (22nd August 2018) - Larsen, Martin A. B.; Skov, Anders B.; Clausen, Christian M.; Ruddock, Jennifer; Stankus, Brian; Weber, Peter M.; Sølling, Theis I.
Abstract: We investigate the ultrafast photoinduced dynamics of the cyclic disulfide 1, 2‐dithiane upon 200 nm excitation by time‐resolved photoelectron spectroscopy and show that the S−S bond breaks on an ultrafast time scale. This stands in stark contrast to excitation at longer wavelengths where the initially excited S1 state evolves as the wavepacket is guided towards a conical intersection with S0 by a torsional motion involving a partially broken bond between the sulfur atoms. This process at lower excitation energy allows for efficient (re‐)population of S0, rendering dithiane intact. At 200 nm, in contrast, the excitation leads to a manifold of higher excited states, Sn, that are primarily of Rydberg character. We are able to follow the gradual transition from the initially excited state to the dissociative receiver state in real time. The Rydberg states are intersected by a repulsive valence state that mediates a transition to the repulsive S2 surface. Therefore, we propose that the resulting diradical will eventually break apart on a longer timescale. The findings imply that upon going from UV−B to UV−C light the structural integrity of the disulfide moiety is compromised and proteins irradiated in this range will not be able to reform the initial tertiary structure, leading to loss of function. Abstract : The gradual transition from the initially excited state to the dissociative receiver state is followed in real time in the cyclic disulfide 1, 2‐dithiane. The Rydberg states are intersected by a repulsive valence state that mediates a transition to the repulsive S2 surface. The resulting diradical will eventually break apart on a longer timescale. Upon UV−C irradiation, the initial tertiary structure is broken, potentially leading to loss of function.